Estudo retrospectivo das micoses e micotoxicoses animais na região sul do Brasil - Gomes, Angelita dos Reis (2012)
This study aims to get to know potential risk factors for dogs and cats presenting positive pathogenic fungus culture diagnosis. A retrospective observational study on fungus infections diagnosed in dogs and cats in southern Brazil between 1980 and 2011 was performed. One thousand seven hundred and thirty-nine clinical sample records of dogs and cats a with suspicion of fungal infections from the Diagnostic and Research Center in Veterinary Mycology (MICVET) and the Regional Diagnosis Laboratory (RDL), both belonging to the Veterinary School of the Pelotas Federal University (FAVET UFPel) were analyzed. Fungal growth was detected in 52,85 % of the samples, of which 37,49 % were pathogenic-related. The winter season presented a 29,49 % pathogenic fungus diagnosis positivity; of these, 48,76 % of the samples were from female animals and 44,11 % of male, whereas 7,13 % were unidentified; also, 79,30 % of the positive samples were of dogs and 20,70 % of cats; the highest positivity rate (26,80 %) occurred in young animals up to two years old. The three most common fungus infections were malasseziosis at a 59,98 % incidence rate, dermatophytosis 18,56 % and sporotrichosis 14,26 %. The species Malassezia Pachydermatis was isolated from 100 % of malasseziosis cases, and 78,98 % malasseziosis cases were otitis-related, most of which in dogs (94,88 %). 24,49 % of dogs were up to two years old, and 54,7 % of canine cases occurred in females. Cocker Spaniel (10,24 %) and Poodle (8,89 %) were the most affected breeds. Dermatophytes were isolated in 18,56 % fungal infections, and Microsporum canis was the most commonly isolated species (57,78 % of dogs and 77,42 % of cats). Dogs presented a 74,38 % rate of cases and the one 24 month age group encompassed 56,67 % of records in dogs and 64,52 % in cats. The most affected breeds were Yorkshire Terrier (10%) and Persian (29,03 %). Sporothrix schenckii infection showed a 13,98 % rate in dogs and an 80,02 % rate in cats. Isolation occurred in 71,25 % cases in male cats; as to dogs, a significant gender-related difference was not found. The two to four year age group showed a 23,75 % occurrence rate. Crossbred animals corresponded to 82,50 % of the cases in cats and 53,85 % in dogs. These data demonstrated that most cats and dogs with fungal infections are young animals, with females showing a greater predisposition; however, no significant differences as to breed, animal fur or seasonality were found. The three most frequently isolated fungi in dogs and cats in southern Brazil were Malassezia pachydermatis, dermatophytes and Sporothrix schenckii.